EXAMINING THE DIMENSIONS OF BIOLOGICAL AGE - Jazwinski, S (Innov Aging, 2018)
Biological age is an expression of physical condition during the lifespan, capturing the heterogeneity among individuals at any given chronological age. Quantification of biological age has been accomplished in various ways. Taking an approach that considers integrated function as an emergent property of an aging system, we have employed a frailty/deficit index for this purpose. This index encapsulates the variation in patterns of aging across groups and across individuals as an intrinsic feature of the measure. It also facilitates the identification of underlying mechanisms. One of these is the increased energetic demand of maintenance of integrated function with declining health in the elderly, which supports the premises underpinning the construction of the index. This mechanism operates differently in males and females, which is associated with different mitochondrial functions. Another mechanism lies at the interface with the environment, the gut microbiome, which adjusts its complexity in parallel with its host.